Post-consolidation process for modifying microscale and mesoscale parameters of 3D printed composite materials - Yudhanto, Arief; Aldhirgham, Alwaleed; Feron, Eric; Lubineau, Gilles (Frontiers in Materials, 2023)
The advancement in additive manufacturing technology (3D printing) has enabled us to fabricate a reasonably good part using continuous fiber-reinforced matrix composites. Unfortunately, most of the 3D-printed composite parts inherently possess a large number of voids originating from the trapped air within and between molten composite beads during the deposition stage. Removing the voids has thus become a key challenge in attempt to apply the 3D printed composite parts for fabricating stiff/strong load-bearing structures. Here, we employed a classical process, viz. compression molding, to post-consolidate 3D-printed continuous carbon fiber-reinforced polyamide (CFPA), and to investigate the implication in terms of microscale parameters (void content) and mesoscale parameters (mechanical properties, plasticity, damage) using matrixdominated lay-up of [±45] 2s . We found that the proposed post-consolidation process could reduce the void of 3D-printed CFPA from 12.2% to 1.8%, enhancing the shear modulus and shear strength by 135% and 116%, respectively. The mesoscale analysis shows that, albeit less ductile, the post-consolidated CFPA laminate was more resistant to damage than the 3D-printed CFPA. The classical compression molding is thus a promising technique to improve the physical and mechanical performances of 3D-printed composites by reducing the inherent void built-ups.